À propos du titre jry nfr-ḥȝ.t, "préposé à celui à l’avant parfait" - Guigner, Mallaury (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
This paper deals with the title jry nfr-ḥȝ.t , which has been debated for a long time. The aim is to identify all individuals who weared this title from the Old Kingdom until the Late Period. The study of people wearing this title can provide some keys to understand the meaning of the expression jry nfr-ḥȝ.t . Some textual and iconographical informations give an idea of its significance, the period and reason of its creation, even if there are no direct evidence. The reuse of the title during the Late Period can be understood as well.